Biomechanical and biochemical characterization of porcine tracheal cartilage. (30th January 2016) - Hoffman, Benjamin; Martin, Matthew; Brown, Bryan N.; Bonassar, Lawrence J.; Cheetham, Jonathan
Abstract : Objectives/Hypothesis: The trachea is essential to respiratory function and is a mechanically and biochemically complex composite tissue. Tissue‐engineering approaches to treat tracheal diseases require detailed knowledge of the native mechanical and biochemical properties of the trachea. Although the porcine trachea represents an excellent preclinical model, relevant mechanical and biochemical composition are incompletely characterized. Study Design: Experimental. The mechanical and biochemical properties of 12 intact porcine tracheas were determined to characterize their compliance, as well as the aggregate modulus, bidirectional elastic modulus, hydraulic permeability, and biochemical characteristics of individual cartilage rings. Results: Data demonstrate the glycosaminoglycan content of tracheal rings was (mean ± standard deviation) 190 ± 49 μg/mg. Hydroxyproline content was 8.2 ± 3.2 μg/mg, and DNA content was 1.3 ± 0.27 μg/mg, a four‐fold difference between circumferential elastic modulus (5.6 ± 2.0 megapascal [MPa]) and longitudinal composite elastic modulus (1.1 ± 0.7 MPa, P < 0.0001) was also observed. Aggregate modulus (stiffness) of porcine tracheal rings was 1.30 ± 0.28 MPa, and inflationary compliance was 0.00472 ± 0.00188 cmH2 O −1 . Conclusion: This study presents a comprehensive characterization of the relevant biochemical and mechanical properties of porcine tracheal cartilage, which is considered an excellent candidate for xenogenic tracheal graft and a source for tissue‐engineered tracheal reconstruction. The range of parameters characterized in this study agrees with those reported for hyaline cartilage of the airway in other species. These characteristics can be used as quantitative benchmarks for tissue‐engineering approaches to treat tracheal disease. Level of Evidence: NA. Laryngoscope, 126:E325–E331, 2016